Spetsificheskie koordinatsionnye sposobnosti kak kriterii prognozirovaniya sportivnykh dostizhenij futbolistov - Lyakh, V. I.; Vitovski, Z.; Zhmuda, V. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The results of three-year researches are submitted in the article which purposes were: 1) the development and the substantiation of sports-motor tests for an estimation of various specific coordination properties which would be suitable during screening and selection of young, highly skilled soccer players; 2) an establishment of reliability and information of the selected tests; 3) the definition of the variability of parameters of the reliability and information of the tests determining different coordination properties, depending on the accepted criteria; 4) the finding of forecast ability of separate tests and parameters of the seven specific coordination properties at young soccer players aged 12 - 13 up to 14 - 15, and also 16 - 17 up to 19 - 20 years subjected to preliminary deep selection. There were 26 soccer players aged 16 - 17 preliminary selected in sports school of city of Zabrze from 400 young men has taken part in the three-year researches in 1998-2001. They appreciably outstripped their peers in parameters of the technical-tactical skills and in the level of the development of the coordination properties. The high forecasting force both separate attributes of coordination properties, and the total estimation of special coordination preparedness were found on the basis of the battery of tests in the carried out researches.